Research with a Purpose: A Reply to My Critics - Baert, Patrick (Human studies, 2009)
Throughout Philosophy of the social sciences: towards pragmatism, my argument has been that the naturalist line of argument is awed, partly because recent developments in analytical philosophy jeopardise any search for a neutral algorithm of scientic method, partly because the natural sciences are characterised by immense diversity across and within disciplines, and partly because the naturalist line of argument erroneously presupposes that social research is primarily, if not exclusively, an explanatory endeavour. [...]my main reservation about the so-called scientic method is grounded in empirical studies of scientists at work, and it is directed against the notion of a universal scientic method (which in turn is based on some elusive notion of the essence of science). [...]I referred to science studies to call attention to the fact that closer investigations of the practice of science make it less convincing to talk about a unifying scientic method within the natural sciences. [...]I emphasised that research can aim at very different objectives and that we ought to celebrate, rather than condone, this diversity.